DURABILITY CHARACTERISTICS OF CONCRETE ADMIXED WITH WOLLASTONITE MINERAL - Kuldasheva Aziza; Kuldashev Kh; Kuldasheva Aziza (European Journal of Life Safety and Stability (2660-9630), 2021)
Several materials as naturally occurring minerals and either industrial wastes have been investigated for making durable concrete material. The present investigation has been aimed to determine the influence of wollastonite on properties of concrete such as strength, permeability and durability over a range of water-binder (w/b) ratios and cement replacement.